Data Encryption Method Using Environmental Secret Key with Server Assistance. Issue 3 (2nd July 2016) - Tsai, Kun-Lin; Leu, Fang-Yie; Tsai, Shun-Hung
Abstract: Data encryption is an effective method for enterprises and government offices to protect their important information from being lost or leaked, especially when data is transmitted on the Internet. In this paper, we propose a novel data encryption/decryption method, named theD ata Encryption Method usingE nvironmentalS ecretK ey with Server Assistance (DESK for short), which provides users with an environmental key of a trusted computer and a group key created for an authorized group to encrypt their data. In the DESK, the important parameters are separately stored and hidden in server and the trusted computer to avoid them from being cracked easily. The proposed method not only protects the important data from being loss, but is also able to resist replay attack and eavesdropping attack. The DESK has a very high security level, which is practically useful in homeland security.